Thermal change assessment in the pulp chamber during orthodontic bonding with different light curing sources (An in vitro study) - Abduljabbar, Omar Fawzi; Bakr, Diyar Kh.; Saleem, Sazan Sh. (Zanco Journal of Medical Sciences (ZJMS), 2017)
Background and objective: Thermal change in pulp chamber with the use of light cured adhesives is one of the contemporary concerns for orthodontists. This study aimed to evaluate intra pulpal temperature rises during bracket bonding using three different light sources. Methods: Sixty intact-extracted mandibular premolars were divided into three groups of twenty teeth for each. Orthodontic brackets were bonded to the buccal surface of all the teeth with Transbond XT adhesive applying a constant force, first group light cured with halogen light, in second group light emitting diode was used, in third group plasma, arc light was used. The measurements were taken with a J-type thermocouple wire, placed in the center of the pulp chamber and connected to a data plugger. Results: Statistical analysis showed that temperatures of pulp chamber change were influenced by a type of light source. The intra pulpal temperature changes for halogen was higher than a light emitting diode and both were higher than plasma arc. All the groups revealed a significant difference between each other. Conclusion: Orthodontic bonding with using different light source did not exceed the critical 5.5° C temperature rise that may induce a thermal change in the pulp.